2020
DOI: 10.1186/s43058-020-00042-4
|View full text |Cite
|
Sign up to set email alerts
|

Is it time to RE-AIM? A systematic review of economic empowerment as HIV prevention intervention for adolescent girls and young women in sub-Saharan Africa using the RE-AIM framework

Abstract: Background Economic empowerment (EE) HIV prevention programs for adolescent girls and young women (AGYW) in sub-Saharan Africa are gaining traction as effective strategies to reduce HIV risk and vulnerabilities among this population. While intervention effectiveness is critical, there are numerous factors beyond effectiveness that shape an intervention’s impact. The objective of this systematic review was to assess the reporting of implementation outcomes of EE HIV prevention programs for AGYW in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 118 publications
2
20
0
Order By: Relevance
“…We found that many HPV self-collection studies reported internal validity measures [ 45 , 47 50 ]. Consistent with other reviews using the RE-AIM framework [ 35 , 51 ], the majority of the studies in our review reported on the methods used to identify the target populations, sample size, and characteristics of participants. However, the participation rate and characteristics of non-participants, components that reflect external validity, were rarely reported in studies.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…We found that many HPV self-collection studies reported internal validity measures [ 45 , 47 50 ]. Consistent with other reviews using the RE-AIM framework [ 35 , 51 ], the majority of the studies in our review reported on the methods used to identify the target populations, sample size, and characteristics of participants. However, the participation rate and characteristics of non-participants, components that reflect external validity, were rarely reported in studies.…”
Section: Discussionsupporting
confidence: 71%
“…Additionally, limited reporting on characteristics of non-participants limits the ability to identify populations that are not engaged in or being reached by these interventions. In an effort to address broad access to interventions and include subgroups of the target population that are most in need of such interventions, researchers need to improve on the reporting of the characteristics of non-participants in an intervention study [ 35 ]. One way to do so is to utilize a participatory approach involving end-users of these interventions in designing and implementating interventions adapted to their contexts and needs [ 53 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This provides a premise for building capacity for economic evaluation in sustainable and institutionalized ways in SSA. Overall, implementation researchers should be mindful of the importance of reporting the cost of their implementing their interventions [ 147 ]. More so, they need to go beyond reporting cost-effectiveness and cost-benefit analyses to demonstrate the long-term economic effects of their interventions [ 148 ].…”
Section: Discussionmentioning
confidence: 99%
“…The RE-AIM framework has been used recently in several systematic reviews to evaluate the internal and external validities of health intervention studies such as weight management intervention [18], physical activity intervention [22,23], worksite health behavior interventions [24], community settings [20], school-based health promotion [25,26], childhood obesity prevention [27][28][29], children dietary interventions with parents [30], injury prevention strategies [31], faithbased intervention [32], mobile phone-based intervention for diabetes self-management [33] and HIV prevention intervention [34]. While encouraging, there is little reporting on its potential use for translating HPV vaccination social media-driven intervention methods into regular practice settings, specifically at the population level.…”
Section: Introductionmentioning
confidence: 99%